A seat suspension with a rotary magnetorheological damper for heavy duty vehicles. (26th September 2016) - Sun, S S; Ning, D H; Yang, J; Du, H; Zhang, S W; Li, W H
Abstract: This paper presents the development of an innovative seat suspension working with a rotary magnetorheological (MR) fluid damper. Compared with a conventional linear MR damper, the well-designed rotary MR damper possesses several advantages such as usage reduction of magnetorheological fluid, low sealing requirements and lower costs. This research starts with the introduction of the seat suspension structure and the damper design, followed by the property test of the seat suspension using an MTS machine. The field-dependent property, amplitude-dependent performance, and the frequency-dependent performance of the new seat suspension are measured and evaluated. This research puts emphasis on the evaluation of the vibration reduction capability of the rotary MR damper by using both simulation and experimental methods. Fuzzy logic is chosen to control the rotary MR damper in real time and two different input signals are considered as vibration excitations. The experimental results show that the rotary MR damper under fuzzy logic control is effective in reducing the vibrations.